Stereotactic body radiotherapy (SBRT) can delay polymetastatic conversion in patients affected by liver oligometastases - Nicosia, Luca; Cuccia, Francesco; Mazzola, Rosario; Figlia, Vanessa; Giaj-Levra, Niccolò; Ricchetti, Francesco; Rigo, Michele; Bonù, Marco; Corradini, Stefanie; Tolia, Maria; Alongi, Filippo (Journal of Cancer Research and Clinical Oncology, 2020)
Purpose: SBRT demonstrated to increase survival in oligometastatic patients. Nevertheless, little is known regarding the natural history of oligometastatic disease (OMD) and how SBRT may impact the transition to the polymetastatic disease (PMD). Methods: 97 liver metastases in 61 oligometastatic patients were treated with SBRT. Twenty patients (33%) had synchronous oligometastases, 41 (67%) presented with metachronous oligometastases. Median number of treated metastases was 2 (range 1–5). Results: Median follow-up was 24 months. Median tPMC was 11 months (range 4–17 months). Median overall survival (OS) was 23 months (range 16–29 months). Cancer-specific survival predictive factors were having further OMD after SBRT (21 months versus 15 months; p = 0.00), and local control of treated metastases (27 months versus 18 months; p = 0.031). Median PFS was 7 months (range 4–12 months). Patients with 1 metastasis had longer median PFS as compared to those with 2–3 and 4–5 metastases (14.7 months versus 5.3 months versus 6.5 months; p = 0.041). At the last follow-up, 50/61 patients (82%) progressed, 16 of which (26.6%) again as oligometastatic and 34 (56%) as polymetastatic. Conclusion: In the setting of oligometastatic disease, SBRT is able to delay the transition to the PMD. A proportion of patients relapse as oligometastatic and can be eventually evaluated for a further SBRT course. Interestingly, those patients retain a survival benefit as compared to those who had PMD. Further studies are needed to explore the role of SBRT in OMD and to identify treatment strategies able to maintain the oligometastatic state.
CRIS-Team Scopus Importer:2025-10-13
Keywords: Liver metastases; Oligometastatic disease; SBRT; Stereotactic body radiotherapy